Exploring ethical frontiers of artificial intelligence in marketing - Harinder Hari; Arun Sharma; Sanjeev Verma; Rijul Chaturvedi (Journal of Responsible Technology)
The pervasiveness of artificial intelligence (AI) in consumers' lives is proliferating. For firms, AI offers the potential to connect, serve, and satisfy consumers with posthuman abilities. However, the adoption and usage of this technology face barriers, with ethical concerns emerging as one of the most significant. Yet, much remains unknown about the ethical concerns. Accordingly, to fill the gap, the current study undertakes a comprehensive and systematic review of 445 publications on AI and marketing ethics, utilizing Scientific Procedures and Rationales for Systematic Literature review protocol to conduct performance analysis (quantitative and qualitative) and science mapping (conceptual and intellectual structures) for literature review and the identification of future research directions. Furthermore, the study conducts thematic and content analysis to uncover the themes, clusters, and theories operating in the field, leading to a conceptual framework that lists antecedents, mediators, moderators, and outcomes of ethics in AI in marketing. The findings of the study present future research directions, providing guidance for practitioners and scholars in the area of ethics in AI in marketing.